PENGARUH KEPATUHAN WAJIB PAJAK, PEMERIKSAAN PAJAK, DAN PENCAIRAN TUNGGAKAN PAJAK TERHADAP PENERIMAAN PAJAK BADAN PADA KANTOR PELAYANAN PAJAK PRATAMA SERANG TAHUN 2012-2016 - Raula Monica; Andi Andi (Jurnal Riset Akuntansi Terpadu, 2019)
The tax revenues at Pratama Serang Tax Office in the latest five years have a decent percentage of accomplishment while the income of the tax itself is keep increasing, this thing is caused by several problem. For instance, taxpayer compliance, tax audit, and the disbursement of tax arrears. The objective of this research is to discover the effect of taxpayer compliance, tax audit, and the disbursement of tax arrears toward the tax revenues. This research applied descriptive statistic method by using quantitative approach. To discover the taxpayer compliance, tax audit, and the disbursement of tax arrears toward tax revenue agency, there will be a data testing by using multiple linear regression, classical assumption test, and the t test in hypothesis test. The result of the research present that the taxpayer compliance, tax audit, and the disbursement of tax arrears’ variable are affecting the tax revenue at Pratama Serang Tax Office in 2012 to 2016.